E-050 Stent assisted coil embolization for large and giant fusiform dissecting aneurysms: a series of 38 cases. (16th November 2010) - Choulakian, A; Eboli, P; Mukherjee, D; Alexander, M
Abstract : Introduction: Fusiform aneurysms present a challenge for treatment since their dome to neck ratios are often less than 1. These are cases that are excluded from most aneurysm series, and prior to intracranial stents were thought not to be treatable by embolization, except by parent artery occlusion. Methods: This is a retrospective analysis of a prospectively collected database of 38 patients who had stent assisted coil embolization of a large or giant fusiform aneurysms. A total of 21 patients had two telescoping stents placed and four patients had three telescoping stents. There is an analysis of the procedure related complications, re-treatments, symptomatology and delayed follow-up. Results: The average aneurysm size treated was 21.4 mm (range 12–61), with an average neck of 18.6 mm. In the periprocedural period there was a 10% complication rate with two strokes and two increased cranial neuropathies. Nine of the patients required re-treatment during a mean follow-up time of 38 months. There were two deaths in the follow-up period: one due to subarachnoid hemorrhage, another presumed due to respiratory arrest. Conclusions: Although stand alone flow diversion devices are being developed and evaluated, stent assisted coil embolization is an effective alternative to fusiform and fusiform dissecting aneurysms. The periprocedural complication rates are reasonable (10%), and although re-treatment is frequently necessary, the long term outcomes are better than the natural history of this disease.